2015
DOI: 10.1002/pros.23095
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retrovirus HERV-K(HML-2) activity in prostate cancer is dominated by a few loci

Abstract: Our findings further underline that HML-2 expression is commonly highly tissue-specific. In prostate cancer, a limited number of loci become activated, especially H22q and ERVK-5. As expressed and non-expressed proviruses do not differ significantly in TFBS, tissue- and tumor-specific expression may be governed primarily by chromatin context. Overexpression of HML-2 H22q is more likely consequence than cause of prostate cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 49 publications
3
44
0
1
Order By: Relevance
“…In comparison with healthy tissues, the higher expression of HERV-K in malignant diseases, like melanomas [27], ovarian cancer [28], breast cancer [29], prostate cancer [30], teratocarcinoma [31], have been investigated. Smoking or ultraviolet C could be the risk factors which may have an influence on the HERV-K expression [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with healthy tissues, the higher expression of HERV-K in malignant diseases, like melanomas [27], ovarian cancer [28], breast cancer [29], prostate cancer [30], teratocarcinoma [31], have been investigated. Smoking or ultraviolet C could be the risk factors which may have an influence on the HERV-K expression [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Although not a common translocation, Tomlins et al identified a prostate tumor with the 5’ end of a HERV-K (HML-2) element on chromosome 22q11.23 fused to ETV1 [199]. This particular HERV-K element is a complex locus with two 5’ LTRs and is quite highly expressed in prostate cancer [200]. Indeed, while a possible function is unknown, this HERV-K locus produces a lncRNA annotated as PCAT-14, for prostate cancer–associated ncRNA transcript-14 [201].…”
Section: Introductionmentioning
confidence: 99%
“…Our results imply that there are more frequent alterations in the copy number of HERV coding sequences than previously appreciated, even for families that apparently have long ceased to be infectious or transpositionally active such as HERV-H and HERV-W (78,79). Overexpression of gene products encoded by these families as well as HERV-K has been documented in a number of conditions, including multiple sclerosis (MS) (18), amyotrophic lateral sclerosis (ALS) (22), rheumatoid arthritis (80), systemic lupus erythematosus (81), schizophrenia (82) and type 1 diabetes (83) and several cancers (84)(85)(86)(87). It remains uncertain whether overexpression of HERVs contributes to the etiology or progression of these diseases.…”
Section: Discussionmentioning
confidence: 99%